(3GdHjGf GdeZQH aj CNHGQ GdeZQHs - (3eMeO GdeQGcTj, CHh YHO Gddg GdeYQha HGHf YPGQj,J (B695 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg MhGOK SfI CQHY hJSYjf heGjI s
(3BNQgG (B:s
(3jfJgi HMhGOK SfI GJfjf hJSYjf hKdGKeGjI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B95s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs